A first-principles study of novel cubic AlN phases. (July 2019) - Liu, Chao; Chen, Mingwei; Li, Jian; Liu, Lingyu; Li, Penghui; Ma, Mengdong; Shao, Cancan; He, Julong; Liang, Tongxiang
Abstract: By a first-principles approach combined with an evolutionary method, four novel cubic AlN phases ( c P16, c F40, c I16, and c I24 AlN) are proposed as promising phases after detailed stability analysis. These four cubic AlN phases exhibit a hardness range of 7.8–17.0 GPa. The anisotropy of their mechanical properties, including Young's modulus, shear modulus, and Poisson's ratio, is systematically studied. Moreover, they are all semiconductors with band gaps smaller than those of experimental phases, and consist of polar covalent Al–N bonds with sp 3 hybridization. Their thermodynamic functions, including enthalpy, Gibbs free energy, and vibrational entropy, are calculated in the temperature range from 0 to 2000 K. Their thermodynamic properties, including Debye temperature and constant-volume specific heat, are investigated. The anisotropy of their minimum thermal conductivities is discussed on the basis of Clarke's model. We hope that this study of the mechanical, electronic, and thermodynamic properties of novel cubic AlN phases will provide guidance for the industrial applications of these four cubic AlN phases. Graphical abstract: With thermodynamically, dynamically and mechanically stable, four cubic AlN phases ( c P16-, c F40-, c I16-, and c I24-AlN) are proposed as the potential phases. They are all semiconductors with band gaps smaller than that of experimental phases as wz and rs. c I16-AlN is an indirect-gap semiconductor, the others are all direct-gap semiconductors. All the four cubic AlN are consisting of polar covalent Al-N bonds with sp 3 hybridized. They all possess good mechanical properties and low anisotropy, especially c P16-AlN. The systematic study of the mechanical, electronic and thermodynamic properties will provide guidance for the industrial applications of these four cubic AlN phases.Image 1 Highlights: Four cubic AlN phases ( c P16, c F40, c I16, and c I24 AlN) are proposed as potential phases via a first-principles approach. They all possess good mechanical properties (Young's modulus, hardness, etc.) and low anisotropy, especially c P16 AlN. They are all semiconductors with small band gaps, and consisting of polar covalent Al–N bonds with sp 3 hybridization.